2022
DOI: 10.21037/tgh-2020-10
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endoscopic resection: a review of endoscopic submucosal dissection (ESD), endoscopic full thickness resection (EFTR) and submucosal tunneling endoscopic resection (STER)

Abstract: Subepithelial lesions are often detected incidentally in patients undergoing an endoscopy. They are common tumors of the gastrointestinal (GI) tract which can originate from different layers of the GI tract wall. These lesions can be further classified based on GI layer of origin and unique histochemical staining. While most are benign and asymptomatic, some of these lesions have malignant potential with distant metastases. However, current diagnostic modalities including endoscopy with biopsy or endoscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“… 1 , 3 Over-the-scope clip-assisted EFTR has been deemed suitable for lesions that are <2 cm in the colorectum. 5 One multicenter prospective study demonstrated that the FTRD device had an overall technical efficacy of 89.5% and an R0 resection rate of 76.9%. 6 In this study, lesions <2 cm had an R0 rate of 81.2% while lesions >2 cm had an R0 rate of 58.11%.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 3 Over-the-scope clip-assisted EFTR has been deemed suitable for lesions that are <2 cm in the colorectum. 5 One multicenter prospective study demonstrated that the FTRD device had an overall technical efficacy of 89.5% and an R0 resection rate of 76.9%. 6 In this study, lesions <2 cm had an R0 rate of 81.2% while lesions >2 cm had an R0 rate of 58.11%.…”
Section: Discussionmentioning
confidence: 99%
“…Submucosal tunnelling endoscopic resection (STER), which has become a popular endoscopic treatment (en-bloc resection) recently, can be applied to small subepithelial tumours (<2 or 3 cm) originating from the muscularis propria, such as schwannoma, leiomyoma, and GIST. [30][31][32] Submucosal tunnelling endoscopic resection is reported to be effective (en-bloc resection rate: 94.6%), less invasive, and has a low risk of adverse events (prevalence of perforation: 5.6%) because tumour resection is performed endoscopically in the submucosal tunnel (artificial submucosal space) without a surgical approach. 33 Submucosal fibrosis caused by MIAB makes STER difficult, as it could cause tunnel damage, thus inducing perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic submucosal dissection is an established minimally invasive procedure for the removal of GI premalignant and malignant lesions, with potential for detailed pathologic evaluation. 1 , 2 Submucosal tunneling endoscopic resection (STER) is a well-established technique within the field of endoscopic submucosal dissection that involves tunnel-exposed, endoscopic full-thickness resection for lesions originating from different layers of the GI tract wall. 3 …”
Section: Case Descriptionmentioning
confidence: 99%
“…Esophageal GISTs account for less than 1% of all GISTs. 2 , 4 , 5 Until recently, treatment options included surveillance, surgical resection, tyrosine kinase inhibitor (TKI), and imatinib, depending on the extent of disease and tumor sensitivity to TKI. 2 , 4 , 6 The advances in third-space endoscopy have led to the development of peroral endoscopic tunnel resection (POET) for the management of submucosal tumors.…”
Section: Case Descriptionmentioning
confidence: 99%